Study abroad, what is considered? - Pratika, Yeyen; Yuniarti, Rahmi (Universitas Muhammadiyah Malang, 2024)
This research aims to explore and describe the motives and experiences of students studying abroad. The respondents were students who studied abroad at their own expense or through scholarship fees. This research uses a qualitative approach by describing data and a quantitative approach using factor analysis. Factor analysis is used to determine factors to consider when studying abroad. The number of respondents was 45 people. The research results show that students' motives for studying abroad are financial, living costs, scholarships, socio-cultural, personal, and administrative.